Modes of occurrence of rare earth elements in peat from Western Siberia; Journal of Geochemical Exploration; Vol. 184, pt. A - Arbuzov S. I. Sergey Ivanovich; Maslov S. G. Stanislav Grigorevich; Finkelman R. B. Robert Barr; Mezhibor A. M. Antonina Mikhailovna; Iljenok (Il'enok) S. S. Sergey Sergeevich; Blokhin M. G. Maksim Gennadjevich; Peregudina E. V. Elena Vladimirovna (2017, 2017)
Title screen